2005
DOI: 10.1080/15459620590961684
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Study of Worker Exposure to a Gaseous Contaminant: Variations on Body Shape and Scalar Transport Model

Abstract: Three-dimensional computational fluid dynamics simulations are used to investigate the distribution and level of contaminant concentrations in the true breathing zone (at the nose and mouth) when toxic airborne contaminants are released within an arm's length in front of the worker who has his back to the airflow. The effects of different body shapes on fluid flow and concentration patterns around the body in a wind tunnel were evaluated and clarified that a sharp body or a block may not be a good surrogate fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 14 publications
4
17
0
Order By: Relevance
“…Studies considering the effect of body geometry on breathing zone concentrations (Brohus, 1997;Li et al, 2003;2005) were not done experimentally, however, they were done numerically using CFD. For example, Li et al (2005) found that rounded body shape (closest approximation to human body) resulted in much lower concentration levels than over simplified bodies.…”
Section: Summary and Conclusion From The Review Of Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Studies considering the effect of body geometry on breathing zone concentrations (Brohus, 1997;Li et al, 2003;2005) were not done experimentally, however, they were done numerically using CFD. For example, Li et al (2005) found that rounded body shape (closest approximation to human body) resulted in much lower concentration levels than over simplified bodies.…”
Section: Summary and Conclusion From The Review Of Literaturementioning
confidence: 99%
“…Studies considering the effect of body geometry on breathing zone concentrations (Brohus, 1997;Li et al, 2003;2005) were not done experimentally, however, they were done numerically using CFD. For example, Li et al (2005) found that rounded body shape (closest approximation to human body) resulted in much lower concentration levels than over simplified bodies. While, studies considered the use of a manikin holding a source in its hands (Guffey, et al 2001;Kim and Flynn, 1992;George et al, 1990;Welling et al, 2001) found dissimilar results when the source located within wake zone than outside the wake zone.…”
Section: Summary and Conclusion From The Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…For instance, they use different levels of velocities and different experimental setups. A static simple manikin without arms, built from basic geometric forms, was used in this study; hence, results can be compared with simulations studies with similar figures (Karaismail, 2011;Li, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Worker exposure and body shape were studied numerically by Li et al (2005). They compared the Eulerian transport model and the Lagrangian trajectory tracking method.…”
Section: Computational Fluid Dynamics Studies (Cfd)mentioning
confidence: 99%